Effect of Body Mass Index on the Prognosis of Liver Cirrhosis - Yin, Yue; Li, Yiling; Shao, Lichun; Yuan, Shanshan; Liu, Bang; Lin, Su; Yang, Yida; Tang, Shanhong; Meng, Fanping; Wu, Yunhai; Chen, Yu; Li, Bimin; et al. (Frontiers in Nutrition, 2021)
Objective: Currently, the association of body mass index (BMI) with the prognosis of liver cirrhosis is controversial. Our retrospective study aimed to evaluate the impact of BMI on the outcome in liver cirrhosis. Methods: In the first part, long-term death was evaluated in 436 cirrhotic patients without malignancy from our prospectively established single-center database. In the second part, in-hospital death was evaluated in 379 cirrhotic patients with acute gastrointestinal bleeding (AGIB) from our retrospective multicenter study. BMI was calculated and categorized as underweight (BMI<18.5kg/m2), normal weight (18.5≤BMI<23.0kg/m2), and overweight/obese (BMI≥23.0kg/m2). Results: In the first part, Kaplan-Meier curve analyses demonstrated a significantly higher cumulative survival rate in overweight/obese group than normal weight group (P=0.047). Cox regression analyses demonstrated that overweight/obesity was significantly associated with decreased long-term mortality compared with normal weight group [hazard ratio (HR)=0.635; 95% confidence interval (CI): 0.405-0.998; P=0.049], but not an independent predictor after adjusting for age, gender, and Child-Pugh score (HR=0.758; 95%CI: 0.479-1.199; P=0.236). In the second part, Kaplan-Meier curve analyses demonstrated no significant difference in the cumulative survival rate between overweight/obese and normal weight groups (P=0.094). Cox regression analyses also demonstrated that overweight/obesity was not significantly associated with in-hospital mortality compared with normal weight group (HR=0.349; 95%CI: 0.096-1.269; P=0.110). In both of the two parts, Kaplan-Meier curve analyses demonstrated no significant difference in the cumulative survival rate between underweight and normal weight groups. Conclusion: Overweight/obesity is modestly associated with long-term survival in cirrhotic patients, but not an independent prognostic predictor. There is little effect of overweight/obesity on the short-term survival of cirrhotic patients with AGIB.